The effect of gender-targeted conditional cash transfers on household expenditures: Evidence from a randomized experiment - Alex Armand; Orazio P. Attanasio; Pedro M. Carneiro; Valérie Lechene (Centre for Microdata Methods and Practice (cemmap), 2018)
This paper studies the differential effect of targeting cash transfers to men or women on the structure of household expenditures on non-durables. We study a policy intervention in the Republic of Macedonia, offering cash transfers to poor households, conditional on having their children attending secondary school. The recipient of the transfer is randomized across municipalities, with payments targeted to either the mother or the father of the child. We show that the gender of the recipient has an effect on the structure of expenditure shares. Targeting transfers to women increases the expenditure share on food by about 4 to 5 percentage points. At low levels of food expenditure, we observe a shift towards a more nutritious diet as a result of targeting women.
Keywords: D12; D13; E21; O12; 330; CCT; intra-household; gender; expenditure